The need to reshape global food processing: a call to the United Nations Food Systems Summit. - Monteiro,CA; Lawrence,M; Millett,C; Nestle,M; Popkin,BM; Scrinis,G; Swinburn,B (BMJ Glob Health, 2021)
In the modern, globalised food system, useful types of industrial food processing that preserve foods, enhance their sensory properties and make their culinary preparation easier and more diverse, have been and are being replaced by food ultra-processing.The main purpose of food ultra-processing is to increase profits by creating hyperpalatable and convenient food products that are grossly inferior imitations of minimally processed foods and freshly prepared dishes and meals.In the last decades, obesity, type 2 diabetes and related diseases have become global epidemics, leading the health systems of many countries to or beyond breaking point.Taken together, the totality of evidence summarised here shows beyond reasonable doubt that increased consumption of ultra-processed foods is a major contributor to the pandemic of obesity, type 2 diabetes and related diseases.The 2021 UN Food System has a unique opportunity to urge countries to implement policy interventions required to reduce ultra-processed food production, distribution and consumption, while simultaneously making fresh or minimally processed foods more available, accessible and affordable.